The Outcome of Papillary Thyroid Cancer Associated with Graves' Disease: A Case Control Study. (8th May 2018) - Menon, Riju; Nair, C. Gopalakrishnan; Babu, Misha; Jacob, Pradeep; Krishna, G. Praveen
Abstract : Introduction . Thyroidectomy is now a less popular therapeutic option for Graves' disease. The frequency of thyroid nodule and the cancer risk of these nodules accompanying Graves' disease are controversial. The outcome of thyroid cancers coexisting with Graves' disease is debated. Study Design . Designed as retrospective case control study of papillary thyroid cancers associated with Graves' disease and those with euthyroid background. Pathological characteristics and outcome of papillary thyroid cancers in the two groups were compared. Results . The tumour characteristics did not differ significantly in the groups. The patients were followed for a mean period of 77.32 months and found significant incidences of disease progression in patients with papillary thyroid cancer associated with Graves' disease (p = 0.034 ; OR 2.747, CI 1.078–7.004). Disease progression as new distant metastases mostly in skeletal locations was high in this group compared to euthyroid group (p = 0.027 ; OR 4.121, CI 1.008–15.600). There was higher incidence of cumulative metastatic diseases in papillary thyroid cancer associated with Graves' disease. Conclusion . Papillary thyroid cancers associated with Graves' disease show aggressive biological behaviour and favoured site of distant metastases was osseous locations. Early diagnosis by routine screening of Graves' disease patients with ultrasound imaging and aspiration studies is recommended.